MOTIVATIONS TO PARTICIPATE IN COLLECTIVE AGRICULTURAL MARKETING IN HUNGARY - Tóth, Anikó; Forgács, Csaba; Fertő, Imre (Economics of Agriculture, 2011)
The paper investigates the motivations of players within agri-food chain to participate in collective agricultural marketing actions using a survey. Our main findings are follows. Estimations show that being member in a lobby group positively influences the participation in collective agricultural marketing programs. Financial support, product developing, finding partner contacts with marketing chains and new partners have strong positive effect in the satisfaction in collective agricultural actions. Finally, membership of a lobby group and the size of firms or associations have positive impact on the willingness to pay for collective marketing actions.